Innovations in Snake Venom-Derived Therapeutics: A Systematic Review of Global Patents and Their Pharmacological Applications - Diana Carolina Zona Rubio; Diana Marcela Aragón; Izabel Almeida Alves (Toxins)
Active compounds from natural sources, particularly snake venoms, are crucial for pharmaceutical development despite challenges in drug discovery. Snake venoms, historically used for medicinal purposes, contain bioactive peptides and enzymes that show therapeutic potential for conditions such as arthritis, asthma, cancer, chronic pain, infections and cardiovascular diseases. The objective of this study was to examine pharmacological and biomedical innovations by identifying the key research trends, the most studied snake species, and their therapeutic applications. A systematic review of patents related to snake venoms was conducted using the European Patent Office database, Espacenet, covering 2014 to mid-2024. The search employed the keyword “venom,” applying IPC classification A61K38/00, resulting in 31 patents after screening. A PubMed survey on “snake venom derivatives innovations” was conducted to compare the scientific literature volume with the identified patents. This review highlights the therapeutic potential of snake venom-derived products for coagulation disorders, cancer, inflammation, and pain management. Despite challenges in pharmacokinetics and venom variability, advancements in biotechnology offer promise for personalized therapies. The future of snake venom-based treatments appears promising for addressing complex medical conditions.